EPISTEMOLOGI KURIKULUM PRODI KPI JURUSAN DAKWAH DAN KOMUNIKASI STAIN PURWOKERTO - Abdul Basit (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2014)
An innovation of a curriculum of a Study Program in a higher education institution is necessary to fulfill the needs of stakeholders that always change and develop. However, this change needs deep consideration and research because curriculum is a fundamental aspect in education and it is a means ofmea suring, evaluating, and understanding all education processes. Curriculum change in Communication and Islamic Broadcasting Program has already had an epistemological scientific basis. In its planning, the change of curriculum is based on the change of national and institutional regulations as well as the development of communication science. Meanwhile, its structure of knowledge is developed from the integration of religion, da’wa, and communication sciences. This structure is derived from learning objectives in Communication and Islamic Broadcasting Program. In implementing curriculum, lecturers have referred to competencies students have to master and have used appropriate materials developed from the structure of knowledge to be developed in Communication and Islamic Broadcast ing Program. Moreover, to improve lecturers’ capacity and professionalism, STAIN Purwokerto facilitates the lecturers to continue their study in doctoral programs and to join training on active learning. However, there are some aspects that should be evaluated, such as lesson plan, implementation of learning strategy, and monitoring students’ development. Finally, regular evaluation is needed to improve the curriculum of Communication and Islamic Broadcasting Program.